Net clinical benefit of new oral anticoagulants (dabigatran, rivaroxaban, apixaban) versus no treatment in a ‘real world’ atrial fibrillation population: A modelling analysis based on a nationwide cohort study - Banerjee, Amitava; Lane, Deirdre A.; Torp-Pedersen, Christian; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2012)
The concept of net clinical benefit has been used to quantify the balance between risk of ischaemic stroke (IS) and risk of intracranial haemorrhage (ICH) with the use oral anticoagulant therapy (OAC) in the setting of non-valvular atrial fibrillation (AF), and has shown that patients at highest risk of stroke and thromboembolism gain the greatest benefit from OAC with warfarin. There are no data for the new OACs, that is, dabigatran, rivaroxaban and apixaban, as yet. We calculated the net clinical benefit balancing IS against ICH using data from the Danish National Patient Registry on patients with non-valvular AF between 1997–2008, for dabigatran, rivaroxaban and apixaban on the basis of recent clinical trial outcome data for these new OACs. In patients with CHADS2=0 but at high bleeding risk, apixaban and dabigatran 110 mg bid had a positive net clinical benefit. At CHA2DS2-VASc=1, apixaban and both doses of dabigatran (110 mg and 150 mg bid) had a positive net clinical benefit. In patients with CHADS2 score≥1 or CHA2DS2-VASc≥2, the three new OACs (dabigatran, rivaroxaban and apixaban) appear superior to warfarin for net clinical benefit, regardless of risk of bleeding. When risk of bleeding and stroke are both high, all three new drugs appear to have a greater net clinical benefit than warfarin. In the absence of head-to-head trials for these new OACs, our analysis may help inform decision making processes when all these new OACs become available to clinicians for stroke prevention in AF. Using ‘real world’ data, our modelling analysis has shown that when the risk of bleeding and stroke are both high, all three new drugs appear to have a greater net clinical benefit compared to warfarin.The editorial process for this article was fully handled by Prof. Christian Weber, Editor-in-Chief.
Keywords: Dabigatran; rivaroxaban; apixaban; atrial fibrillation; stroke prevention